Phytoplankton community response to seasonal eutrophication in Maninjau Lake, West Sumatra, Indonesia - PUTI SRI KOMALA; TRI RETNANINGSIH SOEPROBOWATI; NOVERITA DIAN TAKARINA; LUKI SUBEHI; MARTA WOJEWODKA‑PRZYBYL; BUDHI PRIMASARI; TIVANY EDWIN; LIA ARLINA; REGINA MARDATILLAH (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Komala PS, Soeprobowati TR, Takarina ND, Subehi L, Wojewodka‑Przybyl M, Primasari B, Edwin T, Arlina L, Mardatillah R. 2026. Phytoplankton community response to seasonal eutrophication in Maninjau Lake, West Sumatra, Indonesia. Biodiversitas 27 (2): d270232. https://doi.org/10.13057/biodiv/d270232. The aim of this study is to analyze the seasonal trophic status of Maninjau Lake using the Comprehensive Trophic Status Index (CTSI) and to examine its spatial and temporal relationship with the phytoplankton community structure. The water and phytoplankton samples were collected from 10 sampling points in accordance with SNI 6989-57-2008 and the ecological protocol. Results show that CTSI values ranged from 62.59 to 73.28, indicating eutrophic to hypereutrophic conditions. The trophic sub-indices showed TSI-TP values of 53.24-82.20, TSI-TN values of 50.97-61.49, and TSI-Chl-a values of 52.98-62.07. Based on spatial analysis, the trophic status is relatively homogeneous across all sampling locations, indicating widespread nutrient loading in the lake. On the other hand, higher CTSI values during the rainy season and temporal variation of CTSI are significant. The increase in CTSI was associated with a change in phytoplankton dominance from Bacillariophyceae under eutrophic conditions to Cyanophyceae under hypereutrophic conditions, reflecting tolerance to increased nutrient concentrations. The hypereutrophic status of Maninjau Lake favored opportunistic taxa, as indicated by an increase in the dominance index and decreases in diversity and evenness. Rainfall contributes to shaping phytoplankton community dynamics, affecting the trophic status of the lake. This study highlights that integrating CTSI, phytoplankton ecological indices, and rainfall variability provides a useful framework for assessing air quality degradation and ecosystem stability in tropical lakes.